2009
DOI: 10.1007/s10616-009-9201-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and genotoxic effects of sodium hypochlorite on human peripheral lymphocytes in vitro

Abstract: Chlorination is widely used method in the disinfection of drinking and utility water worldwide. In this study, cytotoxic and genotoxic effects of sodium hypochlorite were investigated by the cytokinesis-block micronucleus assay and chromosomal aberration analysis on human peripheral lymphocytes in vitro. A significant increase in chromosomal aberration frequency was observed in all treatments of NaOCl (0.030, 0.065, 0.100, 0.25, 0.5, 1, 2, 4 lg/mL) at 24 and 48 h compared with the negative control and mitomyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…Index represents parameter for analysis of lymphocyte mitogenic response to cytostatic effects of investigated samples [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…Index represents parameter for analysis of lymphocyte mitogenic response to cytostatic effects of investigated samples [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, cytotoxic and genotoxic effects on human peripheral lymphocytes have been observed in connection with its application. 5 Moreover, it has been shown that a combination of 1% NaOCl + 2% chlorhexidine results in the formation of flocculate precipitates that function as a chemical smear layer, reducing dentinal permeability in the apical third.…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, o nível das pesquisas realizadas em Endodontia tem alcançado padrões de excelente qualidade. Para tanto, existe uma variedade grande nas opções de metodologias, entre elas os testes primários (hematogênicos e de cultura celular), secundários (implantes em subcutâneo de ratos, camundongos e guinea pig) e os tradicionais clínico/microscópicos (dentes de cães, gatos, macacos, cavalos e humanos) (Yesilsoy et al, 1995;Lamano Carvalho et al, 1997;Suguimoto, 1997;Bianconcini;Gavini, 2001;Önçag et al, 2003;Ribeiro et al 2004;Gomes-Filho et al, 2008;Gül et al, 2009).…”
Section: Discussionunclassified
“…Experimentos com culturas celulares (fibroblastos, macrófagos, osteoblastos, linfócitos) têm sido empregados para avaliação da citotoxicidade de diversos materiais, entre eles as soluções irrigadoras utilizadas na terapia endodôntica (Heling et al, 2001;Ribeiro, 2003;Burgos, 2005;Hernandez et al, 2005;Malheiros et al, 2005;Fidalgo et al, 2007;Gül et al, 2009;Simbula et al, 2010).…”
Section: Discussionunclassified
See 1 more Smart Citation